Endothelial Progenitor Cells in Breast Cancer - Monica C Botelho; Helena Alves (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2016)
Recent evidences demonstrated the importance of bone marrow derived Endothelial  rogenitor Cells (EPC), in the contribution to postnatal physiological and pathological neovascularization, and in tumor growth and angiogenesis. These cells are recruited undifferentiated, in response to systemic or chemoactractive signals, such as Vascular Endothelial Growth Factor (VEGF), they lodge in the growing or lesioned tissue and  ifferentiate into endothelial cells in response to local stimuli and cell-cell interactions.The extent and the significance of the EPCs contribution for the growing of most tumors, including those of the breast, are still not fully defined. We analyzed the peripheral blood of breast cancer patients and found that they have circulating EPCs. We also found an  association between expression of AC133+Kdr+ and VEGF plasma levels in these patients. Strategies to impair the mobilization and incorporation of EPCs into breast tumors may contribute to halt the growth of these tumors. Pubmed link: https://www.ncbi.nlm.nih.gov/pubmed/26878074